2022
DOI: 10.1186/s41479-022-00096-z
|View full text |Cite
|
Sign up to set email alerts
|

Multi-drug resistant gram-negative bacterial pneumonia: etiology, risk factors, and drug resistance patterns

Abstract: Bacterial pneumonia is one of the most serious public health issues owing to its medical and economic costs, which result in increased morbidity and mortality in people of all ages around the world. Furthermore, antimicrobial resistance has risen over time, and the advent of multi-drug resistance in GNB complicates therapy and has a detrimental impact on patient outcomes. The current review aimed to summarize bacterial pneumonia with an emphasis on gram-negative etiology, pathogenesis, risk factors, resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 132 publications
1
32
0
1
Order By: Relevance
“…Pneumonia represents a serious public health issue that is associated with high medical burden and substantial economic costs, in addition to hospitalizations and mortality in individuals of all age groups [ 10 ]. Herein, we studied hospitalizations and in-hospital mortality in patients with main and secondary diagnoses of pneumonia in Italy over a 10-year period spanning 2010–2019.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumonia represents a serious public health issue that is associated with high medical burden and substantial economic costs, in addition to hospitalizations and mortality in individuals of all age groups [ 10 ]. Herein, we studied hospitalizations and in-hospital mortality in patients with main and secondary diagnoses of pneumonia in Italy over a 10-year period spanning 2010–2019.…”
Section: Discussionmentioning
confidence: 99%
“…Controlling bacterial infection and killing the activity of pathogenic bacteria are the principles of medication for the treatment of MDR Gram-negative ( G −) bacterial pneumonia [ 10 ]. The results of this study showed that after treatment, the total bacterial clearance rate of the observation group was 90.14%, which was significantly higher than that of the control group, which was 77.61%, and the time for body temperature to return to normal, the time for disappearing rales, the time for leukocyte recovery, and the time for X-ray recovery in the observation group were shorter than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Controlling bacterial infection and killing the activity of pathogenic bacteria are the principles of medication for the treatment of MDR Gram-negative (G−) bacterial pneumonia [10].…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks of such bugs in hospital settings, particularly in intensive care units and hematological or surgical wards, are especially cumbersome. In addition, there are already reports of panresistant microbes in community settings, which, together with hospital dissemination, present significant biosafety issues [ 127 ].…”
Section: Dose Of β-Lactams In Critical Illnessmentioning
confidence: 99%